σ-bonded organochromium(III) complexes. Part 2. Preparation and isolation of pyridylmethylchromium(III) complexes containing dien, [15]aneN4 and Aquo ligands - Crouse, Karen Anne; Goh, Lai Yoong (Elsevier, 1985)
σ-Bonded organochromium complexes were prepared by the reaction of the 2-, 3- and 4-pyridylmethyl chlorides (picolyl chlorides) with Lnchromium(II) ions, where L = dien, diethylenetriamine; 15[ane]N4, tetraazacyclopentadecane; and aquo, H2O. Reactions were carried out in alcoholic, partially alcoholic or aqueous media. The air-stable species were isolated as hydrated chlorides of the pyridylmethyl complexes and the N-protonated pyridiomethyl complexes by precipitation or in solution by purification on a Sephadex C-25 ion exchange column. Characterization was by elemental analysis, absorption spectra and product analyses of their decomposition in aqueous solution.